Konsep Dan Peran Istidlal Maqashid Al-Syari’ah Dalam Islam - Halimatus Sa’diyah; Sitti Lailatul Hasanah (HKI IAI Miftahul Ulum Pamekasan, 2022)
The law is a reference in the order of work, its inherent nature makes a person feel bad if he violates it. Of course, each rule contains specific aims and objectives. Islam recognizes this goal by the name maqashid al-shari'ah. Namely an implied meaning in the rules of Shari'a with five formulations, such as protecting religion, soul, mind, property and offspring. This research tries to unravel the concept and role of maqashid al-syari'ah in determining the proposition (istidlal). The nature of this research is library or doctrinal research with descriptive conceptual analysis